PERANCANGAN APLIKASI PARENTAL CONTROL BERBASIS ANDROID - Hidayat, Rahmat (Jurnal Ilmu Komputer, 2023)
Indonesia is currently one of the developing countries as seen from the proliferation of various types of smartphones, a cellular phone that is able to replace computer work and become a necessity today with the support of an operating system that is able to provide wider access. Communication technology also tends to enable wide-scale transformations in human life. This transformation has led to changes in various patterns of human relationships, which are essentially interpersonal interactions. This Parental Control application is an application that can help parents to find out what applications are often used, where children are active, and record incoming and outgoing telephone numbers on children's smartphones. This application is designed on the android platform, using various features available on android smartphones, such as using the GPS (Global Positioning Service) feature to record the position of the child and the SQLite database as a temporary storage medium on the smartphone if the data has not been sent to the server. The data stored on the smartphone will be sent and stored on the server if the smartphone is connected to the internet, and the data can be viewed through a website designed using PHP, HTML, CSS, jQuery, and MySQL. Based on the results of whitebox and blackbox testing that has been done, this application runs as desired. Translated with DeepL.com (free version)